Akurasi Arah Kiblat Pemakaman Desa Ponteh Kecamatan Galis Kabupaten Pamekasan - Hosen .; Eka Nurhalisa (University of Muhammadiyah Sumatera Utara, 2019)
The Cemetery conditions in Ponteh Village, Galis Sub district, Pamekasan Regency do not appear in line and seem messy both from the shaf rows and the kiblah direction of the cemetery. In this article there are two main issues that are the focus of the problem. First, how is the method of determining the burial Kiblah direction at the Cemetery of Ponteh Village, Galis District, Pamekasan Regency. And second, how is the accuracy of the burial Kiblah direction in the Cemetery of Ponteh Village, Galis District, Pamekasan Regency. The location of this study is in three cemeteries in Ponteh Village, Galis District. The method used is qualitative phenomenological approach in the form of descriptive analysis. Research data obtained from interviews, observations and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show; (1) The method used by the community in determining the cemetery kiblah direction is by estimating and beliefs based solely on feelings called the taqribī method by facing westward and then slightly tilted to the north. There is also an excavation of the burial ground following the direction of the cemetery location and the position of the burial ground located next to it. Second, according to the calculation result of Islamic astronomy, the direction of the cemetery Ajih 66º 9 '53.7